Total Arch Replacement With Frozen Elephant Trunk Using a NEW “Brain-Heart-First” Strategy for Acute DeBakey Type I Aortic Dissection Can Be Performed Under Mild Hypothermia (≥30°C) With Satisfactory Outcomes - Shen, Kangjun; Tan, Ling; Tang, Hao; Zhou, Xinmin; Xiao, Jun; Xie, Dongshu; Li, Jingyu; Chen, Yichuan (Frontiers in Cardiovascular Medicine, 2022)
Background: Total arch replacement (TAR) with Frozen elephant trunk (FET) treatment of acute DeBakey type I aortic dissection (ADIAD) is complicated，carries a high complication/mortality risk and remains controversial on the optimal hypothermic level, cerebral perfusion and visceral organ protection strategy. We developed a new strategy named “Brain-Heart-first” in which the surgical procedures and the management of cardiac perfusion/cerebral protection during Cardiopulmonary bypass (CPB) were redesigned, and TAR with FET technique can be performed under mild hypothermia with satisfactory outcomes. Objective: Our aims were to describe a new surgical strategy under mild hypothermia (≥30°C) for the treatment of ADIAD and to report the operative outcomes of 215 patients. Methods: We conducted a retrospective analysis of 215 consecutive cases of ADIAD treated with our new strategy. Results: The durations of CPB, aortic cross-clamping, antegrade cerebral perfusion, operation, mechanical ventilation support and Intensive Care Unit stay were 139.7 ± 52.3 min, 55.6 ± 27.4 min, 14.1 ± 3.1 min, 6.0 ± 1.7 h, 40.0 h and 4.0 d respectively. The 30-day mortality was 9.8%, with cerebral stroke occurring in 9 patients (4.2%)， paraplegia in 1 patient (0.5%) and postoperative renal injury requiring dialysis in 21 patients (9.8%). The blood transfusion of red blood cells and fresh frozen plasma during surgery and the first 24 h after surgery was 4.0u and 200.0ml respectively. Conclusions: The Brain-Heart-first strategy can be widely used with low technical and resource requirements and provides a safe alternative for conventional TAR with FET technique in ADIAD patients with satisfactory operative results.